Liste over anvendte eksterne bedømmere/reviewere på Tidsskriftet Antropologi - Temaredaktionen, (Tidsskriftet Antropologi, 2022)
Liste over anvendte eksterne bedømmere/reviewere på Tidsskriftet Antropologi